European Investment Bank Activity Report 2020 - European Investment Bank (European Investment Bank, 2021)
Our flagship report highlights the European Investment Bank's key contribution to combatting the COVID-19, climate change and development challenges that dominated 2020. It tells the stories of our crisis solutions. Built around 20 stories profiling 30 of our projects or programmes, the report's "Solutions" sections explain how the EU bank responded swiftly and decisively to a year of crises and laid the foundations for future innovation and growth. The stories take you through the Bank's work in innovation, infrastructure, small and medium-sized enterprises, and climate and environment inside the European Union and beyond the EU's borders. Figures are expected outcomes of financed new operations signed in 2020 for the first time based on available data at this stage. All figures are unaudited and provisional.